Eco-spirituality in BhūmiSūkta - Bhandari, Krishna Prasad (JODEM: Journal of Language and Literature, 2021)
The prime concern of this article is to unfold the eco-conscience of Vedic people through the Vedic text. It is to trace out their environmental and ecological awareness. The article aims at perceiving their eco-spiritual consciousness. This study becomes significant to analyze the Vedic literature through naturalistic perspective and it assists the contemporary eco-campaigners to address the eco-peril of this planet. In order to achieve this objective, this study uses the qualitative research paradigm mostly on the thematic interpretation. It has amalgamated the essence of some of the disciplines of naturalistic school of thought. The core conclusion of them is incorporated within the frame of eco-spirituality that becomes the eco-tool to analyze the text. The primary text is the Bhūmi Sūkta (the hymn to the Earth) from the Atharvaveda. After making the eco-reading upon the hymn, it is quite evident that the Vedic people were aware of the biophysical and temporal aspects of the Earth, and the earth ethics was their life principle for coexistence. The conclusion of this study is that the Vedic people had cherished spiritual ecology for due existence of living and non-living things on the earth.